Case report: A novel combination of anomalies in a patient with 22q11.2 deletion syndrome - Byeman, Connor; Ashwath, Ravi (Frontiers in Pediatrics, 2023)
A frequently occurring genetic disorder, 22q11.2 deletion syndrome can manifest with various abnormalities. The range of cardiac anomalies associated with this syndrome is extensive, with conotruncal defects being the most prevalent. In this study, we report the case of a patient with a unique combination of anatomical abnormalities such as crisscross pulmonary arteries, a cervical aortic arch with coarctation of the aorta, and a ventricular septal defect. The patient underwent initial surgical intervention, which resulted in significant clinical improvement.